Expressão e avaliação da atividade da hialuronidase (Poly p 2) do veneno de Polybia paulista (Hymenoptera: Vespidae) em Escherichia coli sob baixas temperaturas - Pinto, Lucas Machado (2021)
Hyaluronidase (HYAL) is an enzyme widely distributed in nature, found in the venom of invertebrates, vertebrates and in human organs and fluids. This enzyme acts as a diffusion factor, through the degradation of hyaluronic acid, which makes up the extracellular matrix of vertebrates, and can thus be used as an adjuvant to increase the dispersion and absorption of injectable pharmacological drugs. Due to the low amounts of hyaluronidase found in nature and its difficult isolation, the production of this enzyme has been carried out through heterologous expression systems, the most common being the bacterium Escherichia coli. However, due to the lack of post-translational machinery, most of the proteins are expressed in E.coli in an insoluble form, requiring the refolding process to become biologically active, which often causes the loss of part of the material. Therefore, aiming at future biotechnological applications of this enzyme, this study sought to obtain and optimize the recombinant expression of hyaluronidase from Polybia paulista wasp venom (rPoly p 2; 39kDa) in E. coli, in soluble and active form, by means of low temperatures of expression – 8ºC, 10ºC and 12ºC. In parallel, the inclusion bodies obtained in these processes were solubilized and the proteins subjected to refolding in order to recover the enzyme activity. The results showed a higher productivity of rPoly p 2 in soluble and active form when expressed at 10ºC for 48h, compared to temperatures of 8 and 12ºC. On the other hand, the inclusion body solubilization and refolding treatments were not efficient for the enzyme recovery under the conditions tested here. The evaluation and comparison of enzyme activity levels between treatments showed significant levels of rPoly p 2 activity from the soluble fractions in relation to those obtained from the refolding processes and from the positive control (ryPoly p 2) expressed in Komagataella phaffii yeast. However, none of the treatments reached the levels of hyaluronidase activity observed in the crude venom extract of P. paulista. These data, in addition to showing the feasibility of using the prokaryote system in the production of this enzyme in its soluble form, also indicate that a significant saving in the costs of purification of this protein can be achieved, which is extremely relevant in biotechnological terms.